Percepción del paciente acerca de la calidad de atención que brinda la enfermera en el servicio de oncología del Instituto Regional de Enfermedades Neoplasicas - Trujillo - Pilco Sánchez, Milagritos Yovana (2019)
The present descriptive research study was conducted at the National Institute of Neoplastic Diseases of the District of Trujillo, Department of La Libertad, from May to October 2017, with the objective of determining the level of perception of the patient about quality of attention provided by the nurse in the Oncology service of the Regional Institute of Neoplastic Diseases of Trujillo 2017, the sample consisted of 88 patients who were hospitalized for the first time in the oncology service during the period of one week, the following was used instrument: Perception of the oncological patient about the quality of care of the nurse in the Regional Institute of Neoplastic Diseases of Trujillo 2017. Finding the following conclusions: 69.3 percent of patients their level of perception about quality of care is good, followed by 30.7 percent of patients their level of perception about The attention span is regular, and no user presented a level of perception of poor quality of care, within the interpersonal component 71.6 percent of users their level of perception of quality of care is good, 28.4 percent of patients their level of perception on quality of care is regular, and no patient presented a level of perception about poor quality of care, in the component around 69.3 percent of patients their level of perception of quality of care is good, 30.7 percent of patients their level of perception of quality of care is regular and no user presented a level of perception about poor quality of care.